Assessing muscle-specific potassium concentrations in human lower leg using potassium magnetic resonance imaging - Gast, Lena; Baier, Laura-Marie; Chaudry, Oliver; Meixner, Christian; Müller, Max; Engelke, Klaus; Uder, Michael; Heiß, Rafael; Nagel, Armin Michael (NMR in Biomedicine, 2022)
Noninvasively assessing tissue potassium concentrations (TPCs) using potassium magnetic resonance imaging (39K MRI) could give valuable information on physiological processes connected to various pathologies. However, because of inherently low 39K MR image resolution and strong signal blurring, a reliable measurement of the TPC is challenging. The aim of this work was to investigate the feasibility of a muscle-specific TPC determination with a focus on the influence of a varying residual quadrupolar interaction in human lower leg muscles. The quantification accuracy of a muscle-specific TPC determination was first assessed using simulated 39K MRI data. In vivo 39K and corresponding sodium (23Na) MRI data of healthy lower leg muscles (n = 14, seven females) were acquired on a 7-T MR system using a double-resonant 23Na/39K birdcage Tx/Rx RF coil. Additional 1H MR images were acquired on a 3-T MR system and used for tissue segmentation. Quantification of TPC was performed after a region-based partial volume correction (PVC) using five external reference phantoms. Simulations not only underlined the importance of PVC for correctly assessing muscle-specific TPC values, but also revealed the strong impact of a varying residual quadrupolar interaction between different muscle regions on the measured TPC. Using 39K T2* decay curves, we found significantly higher residual quadrupolar interaction in tibialis anterior muscle (TA; ωq = 194 ± 28 Hz) compared with gastrocnemius muscle (medial/lateral head, GM/GL; ωq = 151 ± 25 Hz) and soleus muscle (SOL; ωq = 102 ± 32 Hz). If considered in the PVC, TPC in individual muscles was similar (TPC = 98 ± 11/96 ± 14/99 ± 8/100 ± 12 mM in GM/GL/SOL/TA). Comparison with tissue sodium concentrations suggested that residual quadrupolar interactions might also influence the 23Na MRI signal of lower leg muscles. A TPC determination of individual lower leg muscles is feasible and can therefore be applied in future studies. Considering a varying residual quadrupolar interaction for PVC of 39K MRI data is essential to reliably assess potassium concentrations in individual muscles.
CRIS-Team Scopus Importer:2022-09-16
Keywords: 7 T; muscle MRI; potassium (; sodium (; tissue potassium concentration; tissue sodium concentration; ultrahigh field strengths

Combined imaging of potassium and sodium in human skeletal muscle tissue at 7 T - Gast, Lena; Volker, Stefanie; Utzschneider, Matthias; Linz, Peter; Wilferth, Tobias; Müller, Max; Kopp, Christoph; Hensel, Bernhard; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2020)
Purpose: To validate the feasibility of quantitative combined potassium (39K) and sodium (23Na) MRI in human calf muscle tissue, as well as to evaluate the reproducibility of the apparent tissue potassium concentration (aTPC) and apparent tissue sodium concentration (aTSC) determination in healthy muscle tissue. Methods: Quantitative 23Na and 39K MRI acquisition protocols were implemented on a 7 T MR system. A double-resonant 23Na/39K birdcage RF coil was used. Measurements of human lower leg were performed in a total acquisition time of TANa = 10:54 min/TAK = 8:06 min and using a nominal spatial resolution of 2.5 × 2.5 × 15 mm3/7.5 × 7.5 × 30 mm3 for 23Na/39K MRI. Two aTSC and aTPC examinations in muscle tissue were performed during the same day on 10 healthy subjects. Results: The proposed acquisition and postprocessing workflow for 23Na and 39K MRI data sets provided reproducible aTSC and aTPC measurements. In human calf muscle tissue, the coefficient of variation between scan and re-scan was 5.7% for both aTSC and aTPC determination. Overall, mean values of aTSC = (17 ± 1) mM and aTPC = (85 ± 5) mM were measured. Moreover, for 39K in calf muscle tissue, (Formula presented.) components of (Formula presented.) = (1.2 ± 0.2) ms and (Formula presented.) = (7.9 ± 0.9) ms, as well as a residual quadrupolar interaction of (Formula presented.) = (143 ± 17) Hz, were determined. The fraction of the fast component was f = (58 ± 4)%. Conclusion: Using the presented measurement and postprocessing approach, a reproducible aTSC and aTPC determination using 23Na and 39K MRI at 7 T in human skeletal muscle tissue is feasible in clinically acceptable acquisition durations.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 7 T; potassium MRI; sodium MRI; tissue potassium concentration; tissue sodium concentration; ultrahigh field strengths

Direct imaging of white matter ultrashort T2∗ components at 7 Tesla - Müller, Max; Egger, Nico; Sommer, Stefan; Wilferth, Tobias; Meixner, Christian; Laun, Frederik Bernd; Mennecke, Angelika; Schmidt, Manuel; Huhn, Konstantin; Rothhammer, Veit; Uder, Michael; Dörfler, Arnd; et al. (Magnetic Resonance Imaging, 2022)
Purpose: To demonstrate direct imaging of the white matter ultrashort T2∗ components at 7 Tesla using inversion recovery (IR)-enhanced ultrashort echo time (UTE) MRI. To investigate its characteristics, potentials and limitations, and to establish a clinical protocol. Material and methods: The IR UTE technique suppresses long T2∗ signals within white matter by using adiabatic inversion in combination with dual-echo difference imaging. Artifacts arising at 7 T from long T2∗ scalp fat components were reduced by frequency shifting the IR pulse such that those frequencies were inverted likewise. For 8 healthy volunteers, the T2∗ relaxation times of white matter were then quantified. In 20 healthy volunteers, the UTE difference and fraction contrast were evaluated. Finally, in 6 patients with multiple sclerosis (MS), the performance of the technique was assessed. Results: A frequency shift of −1.2 ppm of the IR pulse (i.e. towards the fat frequency) provided a good suppression of artifacts. With this, an ultrashort compartment of (68 ± 6) % with a T2∗ time of (147 ± 58) μs was quantified with a chemical shift of (−3.6 ± 0.5) ppm from water. Within healthy volunteers' white matter, a stable ultrashort T2∗ fraction contrast was calculated. For the MS patients, a significant fraction reduction in the identified lesions as well as in the normal-appearing white matter was observed. Conclusions: The quantification results indicate that the observed ultrashort components arise primarily from myelin tissue. Direct IR UTE imaging of the white matter ultrashort T2∗ components is thus feasible at 7 T with high quantitative inter-subject repeatability and good detection of signal loss in MS.
Created from Fastlane, Scopus look-up
Keywords: 7 Tesla; Multiple sclerosis; Myelin; Relaxometry; Ultrashort echo time (UTE); White matter

Feasibility of deuterium magnetic resonance spectroscopy of 3-O-Methylglucose at 7 Tesla - Hartmann, Benedikt; Müller, Max; Seyler, Lisa; Bäuerle, Tobias; Wilferth, Tobias; Avdievitch, Nikolai; Ruhm, Loreen; Henning, Anke; Lesiv, Alexei; Ivashkin, Pavel; Uder, Michael; Nagel, Armin Michael (PLoS ONE, 2021)
Deuterium Magnetic Resonance Spectroscopy (DMRS) is a non-invasive technique that allows the detection of deuterated compounds in vivo. DMRS has a large potential to analyze uptake, perfusion, washout or metabolism, since deuterium is a stable isotope and therefore does not decay during biologic processing of a deuterium labelled substance. Moreover, DMRS allows the distinction between different deuterated substances. In this work, we performed DMRS of deuterated 3-O-Methylglucose (OMG). OMG is a non-metabolizable glucose analog which is transported similar to D-glucose. DMRS of OMG was performed in phantom and in vivo measurements using a preclinical 7 Tesla MRI system. The chemical shift (3.51 ± 0.1 ppm) and relaxation times were determined. OMG was injected intravenously and spectra were acquired over a period of one hour to monitor the time evolution of the deuterium signal in tumor-bearing rats. The increase and washout of OMG could be observed. Three different exponential functions were compared in terms of how well they describe the OMG washout. A mono-exponential model with offset seems to describe the observed time course best with a time constant of 1910 ± 770 s and an offset of 2.5 ± 1.2 mmol/l (mean ± std, N = 3). Chemical shift imaging could be performed with a voxel size of 7.1 mm × 7.1 mm × 7.9 mm. The feasibility of DMRS with deuterium labelled OMG could be demonstrated. These data might serve as basis for future studies that aim to characterize glucose transport using DMRS.
CRIS-Team Scopus Importer:2021-06-18

Hybrid B1+-shimming and gradient adaptions for improved pseudo-continuous arterial spin labeling at 7 Tesla - Meixner, Christian; Eisen, Christian; Schmitter, Sebastian; Müller, Max; Herrler, Jürgen; Hensel, Bernhard; Dörfler, Arnd; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2021)
Purpose: To improve pseudo-continuous arterial spin labeling (pcASL) at 7T by exploiting a hybrid homogeneity- and efficiency-optimized (Formula presented.) -shim with adapted gradient strength as well as background suppression. Methods: The following three experiments were performed at 7T, each employing five volunteers: (1) A hybrid (ie, homogeneity-efficiency optimized) (Formula presented.) -shim was introduced and evaluated for variable-rate selective excitation pcASL labeling. Therefore, (Formula presented.) -maps in the V3 segment and time-of-flight images were acquired to identify the feeding arteries. For validation, a gradient-echo sequence was applied in circular polarized (CP) mode and with the hybrid (Formula presented.) -shim. Additionally, the gray matter (temporal) signal-to-noise ratio (tSNR) in pcASL perfusion images was evaluated. (2) Bloch simulations for the pcASL labeling were conducted and validated experimentally, with a focus on the slice-selective gradients. (3) Background suppression was added to the (Formula presented.) -shimmed, gradient-adapted 7T sequence and this was then compared to a matched sequence at 3T. Results: The (Formula presented.) -shim improved the signal within the labeling plane (23.6%) and the SNR/tSNR increased (+11%/+11%) compared to its value in CP mode; however, the increase was not significant. In accordance with the simulations, the adapted gradients increased the tSNR (35%) and SNR (45%) significantly. Background suppression further improved the perfusion images at 7T, and this protocol performed as well as a resolution-matched protocol at 3T. Conclusion: The combination of the proposed hybrid (Formula presented.) -phase-shim with the adapted slice-selective gradients and background suppression shows great potential for improved pcASL labeling under suboptimal (Formula presented.) conditions at 7T.
CRIS-Team Scopus Importer:2021-08-27
Keywords: 7 Tesla; B1 shimming; pcASL; pTx; ultra-high field strengths; VERSE

Influence of image contrasts and reconstruction methods on the classification of multiple sclerosis-like lesions in simulated sodium magnetic resonance imaging - Ruck, Laurent; Mennecke, Angelika; Wilferth, Tobias; Lachner, Sebastian; Müller, Max; Egger, Nico; Dörfler, Arnd; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2022)
Purpose To evaluate the classifiability of small multiple sclerosis (MS)-like lesions in simulated sodium (Na-23) MRI for different Na-23 MRI contrasts and reconstruction methods. Methods Na-23 MRI and Na-23 inversion recovery (IR) MRI of a phantom and simulated brain with and without lesions of different volumes (V = 1.3-38.2 nominal voxels) were simulated 100 times by adding Gaussian noise matching the SNR of real 3T measurements. Each simulation was reconstructed with four different reconstruction methods (Gridding without and with Hamming filter, Compressed sensing (CS) reconstruction without and with anatomical H-1 prior information). Based on the mean signals within the lesion volumes of simulations with and without lesions, receiver operating characteristics (ROC) were determined and the area under the curve (AUC) was calculated to assess the classifiability for each lesion volume. Results Lesions show higher classifiability in Na-23 MRI than in Na-23 IR MRI. For typical parameters and SNR of a 3T scan, the voxel normed minimal classifiable lesion volume (AUC > 0.9) is 2.8 voxels for Na-23 MRI and 19 voxels for Na-23 IR MRI, respectively. In terms of classifiability, Gridding with Hamming filter and CS without anatomical H-1 prior outperform CS reconstruction with anatomical H-1 prior. Conclusion Reliability of lesion classifiability strongly depends on the lesion volume and the Na-23 MRI contrast. Additional incorporation of H-1 prior information in the CS reconstruction was not beneficial for the classification of small MS-like lesions in Na-23 MRI.
CRIS-Team WoS Importer:2022-11-25

Motion-corrected 23Na MRI of the human brain using interleaved 1H 3D navigator images - Wilferth, Tobias; Müller, Max; Gast, Lena; Ruck, Laurent; Meyerspeer, Martin; Kolkovsky, Alfredo L. Lopez; Uder, Michael; Dörfler, Arnd; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2022)
Purpose: To evaluate the feasibility of motion correction for sodium (23Na) MRI based on interleaved acquired 3D proton (1H) navigator images. Methods: A 3D radial density-adapted sequence for interleaved 23Na/1H MRI was implemented on a 7 Tesla whole-body MRI system. The 1H data obtained during the 23Na acquisition were used to reconstruct 140 navigator image volumes with a nominal spatial resolution of (2.5 mm)3 and a temporal resolution of 6 s. The motion information received from co-registration was then used to correct the 23Na image dataset, which also had a nominal spatial resolution of (2.5 mm)3. The approach was evaluated on six healthy volunteers, whose motion during the scans had different intensities and characteristics. Results: Interleaved acquisition of two nuclei did not show any relevant influence on image quality (SNR of 13.0 for interleaved versus 13.2 for standard 23Na MRI and 176.4 for interleaved versus 178.0 for standard 1H MRI). The applied motion correction increased the consistency between two consecutive scans for all examined volunteers and improved the image quality for all kinds of motion. The SD of the differences ranged between 2.30% and 6.96% for the uncorrected and between 2.13% and 2.67% for the corrected images. Conclusion: The feasibility of interleaved acquired 1H navigator images to be used for retrospective motion correction of 23Na images was successfully demonstrated. The approach neither affected the 23Na image quality nor elongated the scan time and can therefore be an important tool to improve the accuracy of quantitative 23Na MRI.
CRIS-Team Scopus Importer:2022-04-15
Keywords: 23Na MRI; 7 Tesla; brain MRI; interleaved dual-nuclear MRI; motion correction; ultrahigh field strength

Quantitative 7T sodium magnetic resonance imaging of the human brain using a 32-channel phased-array head coil: Application to patients with secondary progressive multiple sclerosis - Wilferth, Tobias; Mennecke, Angelika; Gast, Lena; Lachner, Sebastian; Müller, Max; Rothhammer, Veit; Huhn, Konstantin; Uder, Michael; Dörfler, Arnd; Nagel, Armin Michael; Schmidt, Manuel (NMR in Biomedicine, 2022)
Apparent tissue sodium concentrations (aTSCs) determined by 23Na brain magnetic resonance imaging (MRI) have the potential to serve as a biomarker in pathologies such as multiple sclerosis (MS). However, the quantification is hindered by the intrinsically low signal-to-noise ratio of 23Na MRI. The purpose of this study was to improve the accuracy and reliability of quantitative 23Na brain MRI by implementing a dedicated postprocessing pipeline and to evaluate the applicability of the developed approach for the examination of MS patients. 23Na brain MRI measurements of 13 healthy volunteers and 17 patients with secondary progressive multiple sclerosis (SPMS) were performed at 7 T using a dual-tuned 23Na/1H birdcage coil with a receive-only 32-channel phased array. The aTSC values were determined for normal appearing white matter (NAWM) and normal appearing gray matter (NAGM) in healthy subjects and SPMS patients. Signal intensities were normalized using the mean cerebrospinal fluid (CSF) sodium concentration determined in 37 separate patients receiving a spinal tap for routine diagnostic purposes. Five volunteers underwent MRI examinations three times in a row to assess repeatability. Coefficients of variation (CoVs) were used to quantify the repeatability of the proposed method. aTSC values were compared regarding brain regions and subject cohort using the paired-samples Wilcoxon rank-sum test. Laboratory CSF sodium concentration did not differ significantly between patients without and with MS (p = 0.42). The proposed quantification workflow for 23Na MRI was highly repeatable with CoVs averaged over all five volunteers of 1.9% ± 0.9% for NAWM and 2.2% ± 1.6% for NAGM. Average NAWM aTSC was significantly higher in patients with SPMS compared with the control group (p = 0.009). Average NAGM aTSC did not differ significantly between healthy volunteers and MS patients (p = 0.98). The proposed postprocessing pipeline shows high repeatability and the results can serve as a baseline for further studies establishing 23Na brain MRI as a biomarker in diseases such as MS.
CRIS-Team Scopus Importer:2022-08-19
Keywords: 7 T; brain MRI; multiple sclerosis

Toward accurate and fast velocity quantification with 3D ultrashort TE phase-contrast imaging - Degenhardt, Katja; Schmidt, Simon; Aigner, Christoph S.; Kratzer, Fabian J.; Seiter, Daniel P.; Müller, Max; Kolbitsch, Christoph; Nagel, Armin M.; Wieben, Oliver; Schaeffter, Tobias; Schulz-Menger, Jeanette; Schmitter, Sebastian (Magnetic Resonance in Medicine, 2024)
Purpose: Traditional phase-contrast MRI is affected by displacement artifacts caused by non-synchronized spatial- and velocity-encoding time points. The resulting inaccurate velocity maps can affect the accuracy of derived hemodynamic parameters. This study proposes and characterizes a 3D radial phase-contrast UTE (PC-UTE) sequence to reduce displacement artifacts. Furthermore, it investigates the displacement of a standard Cartesian flow sequence by utilizing a displacement-free synchronized-single-point-imaging MR sequence (SYNC-SPI) that requires clinically prohibitively long acquisition times. Methods: 3D flow data was acquired at 3T at three different constant flow rates and varying spatial resolutions in a stenotic aorta phantom using the proposed PC-UTE, a Cartesian flow sequence, and a SYNC-SPI sequence as reference. Expected displacement artifacts were calculated from gradient timing waveforms and compared to displacement values measured in the in vitro flow experiments. Results: The PC-UTE sequence reduces displacement and intravoxel dephasing, leading to decreased geometric distortions and signal cancellations in magnitude images, and more spatially accurate velocity quantification compared to the Cartesian flow acquisitions; errors increase with velocity and higher spatial resolution. Conclusion: PC-UTE MRI can measure velocity vector fields with greater accuracy than Cartesian acquisitions (although pulsatile fields were not studied) and shorter scan times than SYNC-SPI. As such, this approach is superior to traditional Cartesian 3D and 4D flow MRI when spatial misrepresentations cannot be tolerated, for example, when computational fluid dynamics simulations are compared to or combined with in vitro or in vivo measurements, or regional parameters such as wall shear stress are of interest.
CRIS-Team Scopus Importer:2024-01-12
Keywords: 4D flow MRI; displacement artifact; flow artifact; GIRF; gradient imperfections; PC-UTE

Towards accelerated quantitative sodium MRI at 7 T in the skeletal muscle: Comparison of anisotropic acquisition- and compressed sensing techniques - Utzschneider, Matthias; Müller, Max; Gast, Lena; Lachner, Sebastian; Behl, Nicolas G.R.; Maier, Andreas; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance Imaging, 2021)
Purpose: To compare three anisotropic acquisition schemes and three compressed sensing (CS) approaches for accelerated tissue sodium concentration (TSC) quantification using 23Na MRI at 7 T. Materials and methods: Three anisotropic 3D-radial acquisition sequences were evaluated using simulations, phantom- and in vivo TSC measurements: An anisotropic density-adapted 3D-radial sequence (3DPR-C), a 3D acquisition-weighted density-adapted stack-of-stars sampling scheme (SOS) and a SOS approach with golden-ratio rotation (SOS-GR). Eight healthy volunteers were examined at a 7 Tesla MRI system. TSC measurements of the calf were conducted with a nominal spatial resolution of Δx = (3.0 × 3.0 × 15.0) mm3 and a field of view of (156.0 × 156.0 × 240.0) mm3 for multiple undersampling factors (USF). Three CS reconstructions were evaluated: Total variation CS (TV-CS), 3D dictionary-learning compressed sensing (3D-DLCS) and TV-CS with a block matching prior (TV-BL-CS). Results of the simulations and measurements were compared to a simulated ground truth (GT) or a fully sampled reference measurement (FS), respectively. The deviation of the mean TSC evaluated in multiple ROI (mEGT/FS) and the normalized root-mean-squared error (NRMSE) for simulations were evaluated for CS and NUFFT reconstructions. Results: In simulations, the SOS-GR yielded the lowest NRMSE and mEGT (< 4%) with NUFFT for an acquisition time (TA) of less than 2 min. CS further improved the results. In simulations and measurements, the best TSC quantification results were obtained with 3D-DLCS and SOS-GR (lowest NRMSE, mEGT < 2.6% in simulations, mEGT < 10.7% for phantom measurements and mEFS < 6% in vivo) with an USF = 4.1 (TA < 2 min). TV-CS showed no or only slight improvements to NUFFT. The results of TV-BL-CS were similar to 3D-DLCS. Discussion: The TA for TSC measurements could be reduced to less than 2 min by using adapted sequences such as SOS-GR and CS reconstruction approaches such as 3D-DLCS or TV-BL-CS, while the quantitative accuracy stays comparable to a fully sampled NUFFT reconstruction (approx. 8 min TA). In future, the lower TA could improve clinical applicability of TSC measurements.
CRIS-Team Scopus Importer:2020-11-06
Keywords: 7 tesla; Anisotropic acquisition schemes; Compressed sensing; Image reconstruction; Skeletal muscle; Sodium (